Differential Influence of Early Life and Adult Stress on Urogenital Sensitivity and Function in Male Mice - Fuentes, Isabella M.; Pierce, Angela N.; Di Silvestro, Elizabeth R.; Maloney, Molly O.; Christianson, Julie A. (Frontiers in Systems Neuroscience, 2018)
Experiences of adverse childhood events have been associated with improper output of the hypothalamic-pituitary-adrenal (HPA) axis in adulthood, as well as development of comorbid functional pain disorders. Symptoms of chronic prostatitis/chronic pelvic pain syndrome frequently overlap with those of interstitial cystitis/painful bladder syndrome and symptom severity is often triggered by stress. The objective of this study was to investigate the influence early life stress and acute adult stress on 1) perigenital sensitivity, 2) micturition, 3) anhedonia, and 4) HPA axis regulation and output in male C56Bl/6 mice. Neonatal maternal separation (NMS) was performed for 3 hours a day from postnatal day 1 to 21 and naïve pups remained unhandled during this time. As adults, male mice were tested for referred prostate sensitivity and micturition patterning prior to and 1 and 8 days after exposure to 1 hour of water avoidance stress (WAS). Following testing, prostate and bladder tissues were used for mast cell and Western blot analysis and RT-PCR was performed on mRNA from hypothalamus, amygdala, and hippocampus. Serum corticosterone (CORT) was also measured by enzyme-linked immunosorbent assay (ELISA). A significant increase in perigenital sensitivity and micturition frequency was observed in NMS mice and these measures were not exacerbated by WAS exposure. Exposure to NMS significantly increased mast cell degranulation in both the bladder and prostate. Mast cell degranulation was also increased in naïve prostate tissue following WAS exposure. Cytokine mRNA levels were influenced by both NMS and WAS exposure, though WAS had a larger impact on central gene expression. Protein levels of CRF1 were differentially regulated by NMS and WAS in the bladder and prostate and serum CORT levels were significantly diminished following stress exposure. Taken together, these data suggest that NMS results in neurogenic inflammation and hypersensitivity within the urogenital organs, coupled with diminished gene expression and output from the HPA axis. Future studies of NMS in male mice may provide a useful tool as a preclinical model of male chronic urological pain syndromes for investigating potential pharmacological and interventional therapies.